MICRO INFLUENCERS AND AUTHENTICITY: THE NEW FACE OF TRUST IN SOCIAL MEDIA MARKETING - Sinurat, Donal Anry Jaya; Sihombing, Midian Immanuel; Aprilio, Hardo; Bon, Sergius Fribontius; Agus Oniel Galaska; Sinurat, Jolio Toga Estrada (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The rise of micro-influencers has reshaped the dynamics of social media marketing by shifting the emphasis from celebrity endorsements to authenticity-based consumer engagement. Micro-influencers, typically those with a moderate follower base, are known for fostering closer, more relatable, and interactive relationships with their audiences compared to macro-influencers. This study explores the influence of perceived authenticity, content relevance, and engagement frequency on consumer trust in micro-influencers, particularly on platforms such as Instagram and TikTok. Employing a quantitative descriptive approach, the research gathered insights from young Indonesian social media users who actively follow micro-influencers. The analysis reveals that authenticity plays a central role in trust formation, while content relevance and interaction frequency serve as supporting elements that strengthen consumer perception and engagement. These findings align with the commitment–trust theory and parasocial interaction framework, highlighting that consistent, emotionally engaging, and culturally relevant content is essential in cultivating trust in the digital space. The study contributes to the theoretical discourse on influencer marketing and trust, while offering actionable implications for brands and marketers aiming to build meaningful and loyal consumer relationships. It suggests that in an era marked by increasing commercial saturation and consumer skepticism, authenticity is not merely a strategic advantage, it is a foundational necessity for long-term brand success in social media ecosystems.